Pivotal role for the mTOR pathway in the formation of neutrophil extracellular traps via regulation of autophagy - Itakura, Asako (American Physiological Society, 2013)
Autophagy is an essential cellular mechanism for cell homeostasis and survival by which damaged cellular proteins are sequestered in autophagosomal vesicles and cleared through lysosomal machinery. The autophagy pathway also plays an important role in immunity and inflammation via pathogen clearance mechanisms mediated by immune cells, including macrophages and neutrophils. In particular, recent studies have revealed that autophagic activity is required for the release of neutrophil extracellular traps (NETs), representing a distinct form of active neutrophil death, namely NETosis. Although NET formation is beneficial during host defense against invading pathogens, the mechanisms that promote excessive NETosis under pathological conditions remain ill defined. In the present study, we aimed to characterize the role of the mammalian target of rapamycin (mTOR) in NETosis. As mTOR kinase is known as a key regulator of autophagy in many mammalian cells including neutrophils, we hypothesized that mTOR may play a regulatory role in NET release by regulating autophagic activity. Our data show that the pharmacological inhibition of the mTOR pathway accelerated the rate of NET release following neutrophil stimulation with the bacteria-derived peptide formyl-Met-Leu-Phe (fMLP), while autophagosome formation was enhanced by mTOR inhibitors. This increased mTOR-dependent NET release was sensitive to inhibition of respiratory burst or blockade of cytoskeletal dynamics. Overall, this study demonstrates a pivotal role for the mTOR pathway in coordinating intracellular signaling events downstream of neutrophil activation leading to NETosis.